Pengembangan Media Pembelajaran Dinding Virtual Menggunakan Aplikasi Padlet pada Tema 8 Kelas V SD Negeri 3 Pasar Panguruan T.A. 2022/2023 - Simanjuntak, Eva Betty; Naibaho, Putri Julianti (Peneliti.net, 2023)
The problem examined in this research and development is that teachers rarely use learning media in teaching and learning activities in class, while the media used by teachers is media that is found around the class. This study aims to determine the feasibility, practicality and effectiveness of virtual wall learning media using the Padlet application on Theme 8 Sub-theme 1 Learning 4 for VB class students at SD Negeri 3 Pasar Pangururan. This type of research is a type of research and development (Research and Development) using the ADDIE development model through 5 stages, namely the analysis, design, development, implementation and evaluation stages. The subjects in this study were 18 students in class V B SD Negeri 3 Pangururan Market. Data collection techniques in this study used observation, interviews, questionnaires, test questions and documentation. Based on the results of this research and development includes validation from experts which is an assessment of virtual wall learning media using the Padlet application by material experts, media experts and educational practitioners. The results of the validation by material experts got a final score of 88% with the